Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Carbon sequestration potentials in paddy soil: Rice straw phytolith and phytolith carbon with protozoa abundance - Tianyi Shi; Pan Zhou; Wenyuan Wang; Chunyu Hou; Mei Han; Xuming Pan; Liangzi Cao; Jianye Li; Shichen Sun; Li Wang; Duu-Jong Lee (Bioresource Technology Reports, 2025)

Resource utilization of microcrystalline magnesite: Synthesis of magnesium oxide by malic acid steam-assisted decomposition method for the synergetic adsorption of Congo red dye and Cu(II) ion - Jun Li; Ziyu Zhang; Rongzheng Gao; Xiaohui Li; Guoheng Sun; Ziye Zhou; Runtang Feng; Heqi Qi; Dong Zhang; Zihan Zhao; Shichen Xing; Dongmo Wu; et al. (Environmental Research, 2025)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Combined carbon capture and catalytic oxidative dehydrogenation of propane to propylene conversion through a plug-flow dual-phase membrane reactor - Kangkang Zhang; Shichen Sun; Kevin Huang (Chemical Engineering Journal, 2024)

Expandable polystyrene waste modified iron sludge-based biochar activating multiple free radicals for deep wastewater treatment - Shenglin Bu; Wenzong Liu; Muhammad Rizwan Haider; Xiqi Li; Wenzhe Zhang; Qi Sun; Qiandi Wang; Yuanqiang Guo; Shichen Nie; Aijie Wang (Process Safety and Environmental Protection, 2023)

Coral growth over the past 550 years in the central South China Sea linked to monsoon- and seabird-induced nutrient stress - Yi Liu; Shichen Tao; Ruoyu Sun; Chen-Feng You; Tzu-Hao Wang; Thomas Felis; Wang Zheng; Shaobo Sun; Xiaodong Liu; Qi Shi; Jianxin Zhao; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Acute Transcriptomic and Epigenetic Alterations at T12 After Rat T10 Spinal Cord Contusive Injury - Junkai Xie; Seth Herr; Donghan Ma; Shichen Wu; Han Zhao; Siyuan Sun; Zhixiong Ma; Matthew Yan-lok Chan; Katherine Li; Yang Yang; Fang Huang; Riyi Shi; et al. (Molecular Neurobiology, 2023)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

Identification of candidate genes for panicle length in Oryza sativa L. ssp. japonica via genome-wide association study and linkage mapping - Hongliang Zheng; Shichen Sun; Liangming Bai; Shukun Jiang; Guohua Ding; Tongtong Wang; Hongwei Zhao; Jingguo Wang; Hualong Liu; Luomiao Yang; Yan Jia; Xin Wei; et al. (Euphytica, 2022)

Tissue-derived scaffolds and cells for articular cartilage tissue engineering: characteristics, applications and progress - Xuejian Liu; Haoye Meng; Quanyi Guo; Baichuan Sun; Kaihong Zhang; Wen Yu; Shichen Liu; Yu Wang; Xiaoguang Jing; Zengzeng Zhang; Jiang Peng; Jianhua Yang (Cell and Tissue Research, 2018)

Protective effects of grape seed extract fractions with different degrees of polymerisation on blood glucose, lipids and hepatic oxidative stress in diabetic rats - Zhaoxia Wu; Siyao Shen; Jiaqian Jiang; Dehong Tan; Donghua Jiang; Bing Bai; Xiyun Sun; Shichen Fu (Natural Product Research, 2015)

A fractionation procedure for identifying novel proteins induced by chill stress in Arabidopsis thaliana - Liwen Sun; Shichen Wang; Jinghui Xi; Shuo Yang; Xiangguo Liu; Xin Chai; Hongbao Xin; Baiyi An; Dongyun Hao (Biotechnology Letters, 2009)